Assesment of Construction Safety Management System (CSMS) In Confined Space Tunnel Construction: A Case Study Of Jragung Dam - Indah Wahyuni; Sabrina Nur Hamidah (Universitas Negeri Yogyakarta, 2026)
Construction work on bypass tunnels involves work in confined spaces that pose high-risk hazards, such as toxic gases, noise, electrical hazards, and limited mobility; therefore, the implementation of a Construction Safety Management System (CSMS) is essential to minimize the risk of workplace accidents. Previous research on CMS implementation has primarily focused on open-space construction projects, while studies on confined-space construction—particularly bypass tunnels—remain limited. Additionally, several safety compliance issues were identified during the Jragung Dam project. This study aims to analyze CMS implementation, identify barriers to its adoption, and propose corrective measures in accordance with applicable regulations. The research method used is quantitative with a descriptive approach. Data were obtained through questionnaires, observations, and interviews at the Jragung Dam bypass tunnel construction project in Semarang Regency. The results of the study indicate that seven out of nine components of SMKK implementation fall into the “good” and “effective” categories, while the remaining two components fall into the “fairly good” category. The highest percentage was found in traffic signs and accessories as well as consultation with construction experts at 88%, while the lowest percentage was found in construction safety risk control activities at 75%. This study suggests that the implementation of SMKK in confined spaces needs to be carried out more effectively and in accordance with regulations so that the risk of workplace accidents can be minimized and worker safety better ensured.